The Effect of Teacher Gender on Student Achievement in Primary School - Antecol, Heather; Eren, Ozkan; Ozbeklik, Serkan (Journal of Labor Economics, 2015)
Using data from a randomized experiment, we find that having a female teacher lowers the math test scores of female primary school students in disadvantaged neighborhoods. Moreover, we do not find any effect of having a female teacher on male students’ test scores (math or reading) or female students’ reading test scores, which seems to rule out explanations pertaining to the unobserved quality differences between male and female teachers. Finally, this negative effect seems to persist only for female students who were assigned to a female teacher with a limited math background.